THE RELATIONSHIP BETWEEN ORGANIZATIONAL ETHICAL CLIMATE WITH EMOTIONAL INTELLIGENCE AND EMPOWERMENT IN AL-MUSTOFA INTERNATIONAL UNIVERSITY IRAN - Shahidi, Nima; Mahbubi, M. (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study explores the relationship between organizational ethical climate, emotional intelligence, and empowerment among heads of educational departments at Al-Mustofa International University in Iran. The research aims to examine how an ethical climate within the university influences emotional intelligence and how emotional intelligence, in turn, affects the empowerment of department heads. A quantitative approach was used, with data collected from 60 department heads through a structured survey. The results revealed a moderate positive correlation between organizational ethical climate and emotional intelligence, indicating that a positive ethical environment enhances emotional intelligence among leaders. Furthermore, emotional intelligence was found to have a strong positive correlation with empowerment, suggesting that department heads with higher emotional intelligence feel more empowered in their roles. The study also highlighted a weaker, yet significant, relationship between organizational ethical climate and empowerment, emphasizing the importance of an ethical environment in fostering a sense of empowerment. The findings suggest that universities can benefit from fostering ethical climates and developing emotional intelligence among their leaders. Recommendations for future research include exploring the role of emotional intelligence in other academic settings and conducting longitudinal studies to examine the long-term effects on leadership effectiveness.